1991
DOI: 10.1007/bf00588255
|View full text |Cite
|
Sign up to set email alerts
|

Hypodense bubbles in acute extradural haematomas following venous sinus tear

Abstract: Between January 1982 and December 1989, 12 patients with 13 acute extradural haematomas as a result of injury involving the venous sinuses were treated by the first author. The CT scan appearances in 6 cases were remarkable in that there were large bubbles of low density in the hyperdense haematomas and liquid blood was found during the operation. The possible underlying pathophysiological changes that gave rise to this appearance are discussed. The CT scan appearance and the proximity of the clot to the venou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…13,14 Mixeddensity hematoma has been observed in patients with epidural hemorrhage and is reported to correlate with active bleeding. 15 The hypointense area encapsulated within the hyperintense hematoma is termed the swirl sign and is found in a significant proportion of patients with epidural hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Mixeddensity hematoma has been observed in patients with epidural hemorrhage and is reported to correlate with active bleeding. 15 The hypointense area encapsulated within the hyperintense hematoma is termed the swirl sign and is found in a significant proportion of patients with epidural hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the association of hematoma heterogeneity with acute hematoma growth. In the 1980s, hematoma heterogeneity was observed in patients with traumatic epidural hemorrhage 28,29 , and the mixed density of hematomas has been reported to correlate with active bleeding, which has been validated during the surgical exploration of patients with epidural hemorrhage 30,31 . Of note, similar to the multihematoma fuzzy sign, fukamachi A, et al described a characteristic salt and pepper or flecked patthern of mixed area of hypodensity and hyperdensity, which usually indicates delayed intracranial hematoma after head injury 32 .…”
Section: Discussionmentioning
confidence: 96%
“… 4 11) Other unusual preoperative CT findings indicate possible venous bleeding including bilateral EDHs, 7) and hypodense lesions within hematoma. 5) …”
Section: Discussionmentioning
confidence: 99%